From Rackham to REVEALS: Reflections on Palaeoecological Approaches to Woodland and Trees. (3rd July 2018) - Richer, Suzi; Gearey, Benjamin
ABSTRACT: In this paper we reflect on aspects of palaeoecological approaches to understanding past woodland environments. With increasing requirements for interdisciplinarity in research, and an increase in popular interest in the 'natural environment' such as 'new nature writing', we suggest that palaeoecology is potentially well situated to engage with other audiences and disciplines, and inform wider debates. However, in order to achieve this, we tentatively suggest that palaeoecology should be self-reflexive and examine how current methods, terminology and underlying theoretical perspectives inform (and inhibit) our practice. Using insights from Oliver Rackham's influential woodland studies as focal points, we examine selected aspects of method and theory in palaeoecology and suggest an approach to developing a praxis of woodland palaeoecology. In practical terms, this (1) incorporates other information and alternative perspectives, and is willing to question its methods and ways of thinking, (2) takes account of past and present, differences in the perceptions of the environment, (3) looks to build enriched accounts without privileging one perspective/set of 'data' over another by 'flattening out' knowledge hierarchies, potentially making the discipline more flexible in its outlook and applicability. A short case study from Shrawley Woods, Worcestershire, UK, illustrates the approach and includes the first example of historical documents and oral history accounts being used in the construction of a pollen diagram.